ANALISIS AMANAT DALAM PUISI “PANGGUNG SANDIWARA” KARYA IKA MUSTIKA - Vivin Kusmiati; Nursiti Fatimah; Dida Firmansyah (IKIP Siliwangi, 2018)
This research aims to find out the message contained in the poem